Communication Strategy For Government Members Of The Legislature In Conflict Management In Poso District - Sitti Chaeriah Ahsan; Andi Febri Herawati N; Donal Adrian (International Journal of Artificial Intelligence Research, 2022)
The inter-religious conflict began in Poso Regency on December 24, 1998. The incident occurred because of clashes between youths of different religions. The research aims to analyze the communication strategy of governing council members as opinion leaders in managing various religious conflicts in Poso Regency. Qualitative research methods using observation data collection techniques and in-depth interviews. Data analysis uses the perspective of Miles and Huberman, namely data reduction, data presentation, and conclusion/verification. The results of the study show that the communication strategy of government members of the legislature in preventing conflict in Poso Regency, namely messages conveyed to the public, must be more rational and easy to understand, such as using local accents or languages; showing mutual respect by visiting religious holidays such as Christmas and Eid; helping each other in building houses of worship, trying to calm the community if further conflicts occur and being able to cooperate with the media; and coordinating with community leaders, students, local government (Bupati) and police agencies